Family Business Dynamics in Southeast Asia: A Comparative Study of Indonesia, Malaysia, Singapore, and Thailand - Sukamdani, Nugroho (Centre for Business and Diplomatic Studies (CBDS) Bina Nusantara University, 2023)
The research discussed the literature on family business in four Southeast Asian countries, namely Indonesia, Malaysia, Singapore, and Thailand. The four countries were selected as case studies to contextualize the southeast Asian family business context. In addition, the research perceived that the four countries have similar sociocultural characteristics, potentially providing similar attributes to how family businesses establish and grow. Drawing from literature collected from the Scopus database through the keywords “family business,” “Indonesia,” “Malaysia,” “Thailand,” and “Singapore,” the research provided the dynamics of knowledge production through systemic literature review. A narrative literature review was implemented to provide a high level of abstraction to the literature on family business differences and similarities. The findings show that the theme of succession was widely discussed in the literature. Succession in all four countries still prioritizes members of the family as successors. However, literature in Indonesia provides a more in-depth understanding of the way succession works. The research enriches the present discussion and provides insights for researchers on the research gap in family business issues. At a practical level, the research provides insight for professionals who work in the sector to gain insight into how family businesses work to maintain their entrepreneurial spirit.